Kinesiophobia Severity Categories and Clinically Meaningful Symptom Change in Persons With Achilles Tendinopathy in a Cross-Sectional Study: Implications for Assessment and Willingness to Exercise - Chimenti, Ruth L.; Post, Andrew A.; Silbernagel, Karin Grävare; Hadlandsmyth, Katherine; Sluka, Kathleen A.; Moseley, G. Lorimer; Rio, Ebonie (Frontiers in Pain Research, 2021)
Objectives: (1) Validate thresholds for minimal, low, moderate, and high fear of movement on the 11-item Tampa Scale of Kinesiophobia (TSK-11), and (2) Establish a patient-driven minimal clinically important difference (MCID) for Achilles tendinopathy (AT) symptoms of pain with heel raises and tendon stiffness. Methods: Four hundred and forty-two adults with chronic AT responded to an online survey, including psychosocial questionnaires and symptom-related questions (severity and willingness to complete heel raises and hops). Kinesiophobia subgroups (Minimal ≤ 22, Low 23–28, Moderate 29–35, High ≥ 36 scores on the TSK-11), pain MCID subgroups (10-, 20-, 30-, >30-points on a 0- to 100-point scale), and stiffness MCID subgroups (5, 10, 20, >20 min) were described as median [interquartile range] and compared using non-parametric statistics. Results: Subgroups with higher kinesiophobia reported were less likely to complete three heel raises (Minimal = 93%, Low = 74%, Moderate = 58%, High = 24%). Higher kinesiophobia was associated with higher expected pain (Minimal = 20.0 [9.3–40.0], Low = 43.0 [20.0–60.0], Moderate = 50.0 [24.0–64.0], High = 60.5 [41.3–71.0]) yet not with movement-evoked pain (Minimal = 25.0 [5.0–43.0], Low = 31.0 [18.0–59.0], Moderate = 35.0 [20.0–60.0], High = 43.0 [24.0–65.3]). The most common pain MCID was 10 points (39% of respondents). Half of respondents considered a 5-min (35% of sample) or 10-min (16%) decrease in morning stiffness as clinically meaningful. Conclusions: Convergent validity of TSK-11 thresholds was supported by association with pain catastrophizing, severity of expected pain with movement, and willingness to complete tendon loading exercises. Most participants indicated that reducing their pain severity to the mild range would be clinically meaningful.